Cytomegalovirus kinetics after hematopoietic cell transplantation reveal peak titers with differential impact on mortality, relapse and immune reconstitution. Issue 4 (12th February 2021) - Leserer, Saskia; Bayraktar, Evren; Trilling, Mirko; Bogdanov, Rashit; Arrieta‐Bolaños, Esteban; Tsachakis‐Mück, Nikolaos; Crivello, Pietro; Koldehoff, Michael; Maaßen, Fabienne; Ross, Rudolf Stefan; Fleischhauer, Katharina; Beelen, Dietrich W.; et al.
Abstract: Even in the era of PCR‐based monitoring, prophylaxis, and preemptive therapy, Cytomegalovirus (CMV) viremia remains a relevant cause of non‐relapse mortality (NRM) after allogeneic hematopoietic cell transplantation (HCT). However, studies using binary analysis (presence/absence of CMV) reported contradicting data for NRM, overall survival and leukemia relapse. Here, we analyzed CMV replication kinetics in 11 508 whole blood PCR samples of 705 patients with HCT between 2012 and 2017. Using two independent models based on CMV peak titers and on the time point of first CMV reactivation, we stratified patients into risk cohorts. Each cohort had distinct cellular immune reconstitution profiles and differentiated for relevant clinical outcomes. Patients with high CMV peak titers had significantly reduced overall survival (HR 2.13, 95% CI 1.53–2.96; p < .0001), due to high NRM. Early impaired T cell reconstitution was a risk factor for high CMV peak titers, however relevant CMV viremia also related to boosted T cell reconstitution. Importantly, intermediate CMV peak titers associated with a significantly reduced relapse probability (HR 0.53, 95% CI 0.31–0.91; p = .022). In short, CMV kinetics models distinguished relevant clinical outcome cohorts beyond the R+ serostatus with distinct immune reconstitution patterns and resolve in part contradicting results of previous studies exclusively focused on the presence or absence of CMV.